ELEMENTS IN LIVER TISSUES OF BOWHEAD WHALES ( BALAENA MYSTICETUS ) - Cheryl A. Krone; Paul A. Robisch; Karen L. Tilbury; John E. Stein; Elizabeth A. Mackey; Paul R. Becker; Todd M. O'hara; L. Michael Philo (Marine Mammal Science, 1999)
A bstract Livers from 20 bowhead whales taken in subsistence hunts at Barrow, Alaska, were analyzed for essential and non‐essential elements. Concentrations of essential elements were similar to those found in other cetaceans. Non‐essential element concentrations were generally comparable to other baleen whales and very low compared to most odontocetes. One deviation from this pattern was a relatively high level of hepatic cadmium that may be related to specific dietary factors of this krill‐dependent species. No sex‐related differences were found in element concentrations. Hepatic cadmium and mercury increased with animal length, and significant positive interelement correlations were found between copper/zinc and mercury/selenium. We found a mercury‐toselenium ratio much lower (1:40) than the frequently reported ratio of one to one. The data suggest that further studies of the postulated mercurydetoxifying role of selenium are warranted.